2014
DOI: 10.1002/2013jg002540
|View full text |Cite
|
Sign up to set email alerts
|

Runoff‐mediated seasonal oscillation in the dynamics of dissolved organic matter in different branches of a large bifurcated estuary—The Changjiang Estuary

Abstract: The Changjiang Estuary is a large bifurcated estuary where different hydrodynamic processes influence its South Branch compared to its North Branch. The South Branch is the dominant pathway of Changjiang River discharge, while the shallower and narrower North Branch is dominated by salt water intrusion, especially in the dry season. Absorption and fluorescence spectroscopy were measured along with dissolved organic carbon (DOC) concentrations to characterize the properties of dissolved organic matter (DOM) col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 75 publications
5
80
1
Order By: Relevance
“…2, urban structures across the land-water interface can also result in pulsatile flows of water and materials as a combined consequence of increased runoff from the impervious urban surface and discharges from WWTPs, stormwater drainages, and combined sewer overflows (Paul and Meyer, 2001;Garnier and Billen, 215 2007; Kaushal and Belt, 2012). Although wastewater can bring pulses of OM and nutrients to the receiving urban water systems, its impact on riverine metabolism and CO2 outgassing has not been investigated in many Asian river systems except for a few exploratory studies (Guo et al, 2014;Yoon et al, 2017).…”
Section: Conceptual Framework For Understanding Interactive Effects Omentioning
confidence: 99%
See 2 more Smart Citations
“…2, urban structures across the land-water interface can also result in pulsatile flows of water and materials as a combined consequence of increased runoff from the impervious urban surface and discharges from WWTPs, stormwater drainages, and combined sewer overflows (Paul and Meyer, 2001;Garnier and Billen, 215 2007; Kaushal and Belt, 2012). Although wastewater can bring pulses of OM and nutrients to the receiving urban water systems, its impact on riverine metabolism and CO2 outgassing has not been investigated in many Asian river systems except for a few exploratory studies (Guo et al, 2014;Yoon et al, 2017).…”
Section: Conceptual Framework For Understanding Interactive Effects Omentioning
confidence: 99%
“…When published data of pCO2 were compared between the headwaters and the tributaries feeding into the middle and lower reaches of the major Asian rivers, tributary pCO2 levels (mean: 2,128 atm) tended be higher than those for the headwaters of the 360 both global (mean: 1116 atm) and Asian rivers (mean: 819 atm) (Table 3 and references therein). Some studies have examined the effects of domestic and industrial wastewaters on the chemical composition and lability of riverine organic C (e.g., Guo et al, 2014). By comparing fluorescence excitation-emission matrices (EEMs) of DOM between the branches and tributaries of the Yangtze River estuary, Guo et al (2014) found that labile DOM components delivered by the Huangpu River, a highly polluted tributary, exerted a disproportionately large influence on the biodegradability of DOM in the 365 Yangtze estuary.…”
Section: Effects Of Increasing Water Pollution In Asian River Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50 separate plots will be arranged in this area to create different habitat types (mainly shallow water and vegetated marshes) for bird groups such as Charadriiformes, Anatidae, Ardeidae, and Gruidae. There is a strong salinity gradient in the Dongtan wetland because freshwater runoff in the Yangtze River estuary is substantially higher at the south branch of Chongming Island than the north (Guo et al, 2014;Hu et al, 2014). Surface water salinity increases from <0.5‰ in southern creeks to >25‰ in northern creeks of Dongtan (Guo et al, 2014).…”
Section: Implications For the Design Of Created Coastal Wetlandsmentioning
confidence: 99%
“…The project design involves dividing the area into dozens of plots with differing types of wetlands (mainly vegetated and unvegetated) to meet the habitat demands of various bird groups. Because wetlands in the Yangtze River estuary range widely in salinity (<0.5‰ to >25‰) (Guo et al, 2014), the arrangement of created wetlands of different salinities and different vegetation coverage may influence spatial patterns of carbon uptake and release, thereby affecting conservation of the carbon sink function in the marsh. This study lays a foundation for future spatial design of created wetlands in the Dongtan restoration project.…”
Section: Introductionmentioning
confidence: 99%